An Analysis of the Structural Properties of Modern Emojis and their Relationship to Saussure's Theory of Language - Shahid Hussain .; Dr. Mazhar Abbas (بازیافت, 2023)
<span style="font-size: 12.0pt; line-height: 107%; font-family: "Calibri",sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This research paper explores the structural properties of modern Emojis and their relationship to Saussure's theory of language. Drawing on a range of linguistic and cognitive theories, we analyze the features of modern Emojis that make them unique from traditional linguistic forms such as words and sentences. We also examine the ways in which modern Emojis are processed and interpreted by the human brain, and how their meanings are determined in part by their structural properties and relationships to other signs within a system of communication. Through a cross-cultural analysis of emoji meaning and interpretation, we demonstrate the complex and nuanced nature of visual communication, and its implications for language use in the digital age. Overall, this research sheds light on the unique nature of visual communication as a form of language, and its role in shaping new forms of communication and expression in the digital age.